Review of hydrogen leakage along the supply chain: Environmental impact, mitigation, and recommendations for sustainable deployment - Abdurahman Alsulaiman (The Oxford Institute for Energy Studies, 2024)
Hydrogen is recognized as a pivotal element in the shift toward a low-carbon economy, presenting a clean energy alternative for sectors that are particularly challenging to decarbonize. Nevertheless, hydrogen's efficacy as a sustainable solution faces constraints due to the potential environmental impacts linked to leakage across its supply chain - from production through to end-use. This paper offers a detailed review of hydrogen leakage rates, examines technological and regulatory measures aimed at minimizing leakage, and assesses the environmental implications of hydrogen release into the atmosphere. This paper explains why even minimal hydrogen leakage can exacerbate climate change by prolonging the atmospheric presence of methane and modifying ozone levels, thus producing indirect global warming effects. Addressing these issues necessitates a comprehensive approach encompassing investment in advanced containment materials, improved leak detection systems, retrofitting of existing infrastructure, and stringent regulatory standards. Policy incentives that encourage low-leakage technologies, alongside industry training initiatives, are also essential. Implementing these mitigation strategies will enable stakeholders to reduce the potential environmental risks of hydrogen leakage. Indeed, effective management of hydrogen leakage is critical to ensuring that this clean energy carrier realizes its potential in reducing greenhouse gas (GHG) emissions, contributing to overarching goals of sustainability and climate resilience.
Keywords: 330; Climate Effects of Hydrogen Leakage; How Hydrogen Leaks; Hydrogen Leakage Across the Supply Chain; Impacts of Hydrogen Leakage; Recommendations for Mitigating Hydrogen Leakage; Review of Hydrogen Leakage